Canonical Transient Receptor Potential Channels and Their Link with Cardio/Cerebro-Vascular Diseases - Xiao, Xiong (Biomol Ther (Seoul), 2017)
The canonical transient receptor potential channels (TRPCs) constitute a series of nonselective cation channels with variable degrees of Ca(2+) selectivity. TRPCs consist of seven mammalian members, TRPC1, TRPC2, TRPC3, TRPC4, TRPC5, TRPC6, and TRPC7, which are further divided into four subtypes, TRPC1, TRPC2, TRPC4/5, and TRPC3/6/7. These channels take charge of various essential cell functions such as contraction, relaxation, proliferation, and dysfunction. This review, organized into seven main sections, will provide an overview of current knowledge about the underlying pathogenesis of TRPCs in cardio/cerebrovascular diseases, including hypertension, pulmonary arterial hypertension, cardiac hypertrophy, atherosclerosis, arrhythmia, and cerebrovascular ischemia reperfusion injury. Collectively, TRPCs could become a group of drug targets with important physiological functions for the therapy of human cardio/cerebro-vascular diseases.